The Role of Porphyromonas gingivalis Virulence Factors in Periodontitis Immunopathogenesis: Peran Faktor Virulensi Porphyromonas Gingivalis pada Imunopatogenesis Periodontitis) - Septiwidyati, Tienneke Riana; Bachtiar, Endang Winiati (Dentika: Dental Journal, 2020)
Porphyromonas gingivalis is an anaerobic Gram-negative oral bacterium involved in the pathogenesis of periodontitis. Periodontitis is an infection that is characterized by damage to the supporting tissues of the teeth so that it can cause tooth loss if not given treatment. P. gingivalis locally can invade periodontal tissue and avoid host defense mechanisms. This bacterium has virulence factors which can cause deregulation of innate immune responses and inflammation in the host. The role of P. gingivalis virulence factors such as capsules, fimbriae, lipopolysaccharides, and gingipain in the pathogenesis of periodontitis will be discussed in this paper.